EXPERIENCE IN IMPLEMENTING OF INSTITUTIONAL REPOSITORIES IN UKRAINE (Journal of Information Technologies in Education (ITE), 2015)
The rapid growth in the number of institutional repositories in the world shows that one of the main activities of research institutions and leading educational institutions is to spread there own works in the global information space. Institutional repositories manage, preserve and maintain digital assets and intellectual products, as well as increase the speed and convenience of obtaining the necessary information. This paper describes the modern state of deployment of the institutional repositories in the universities of Ukraine. The author analyzes registries OpenDOAR,ROAR, rating Ranking Web of Repositories. She investigates the following indicators: access level,number of matherials, types of resources, availability of statistics service. Article contains classification of the existing electronic libraries of scientific and educational institutions. The main problems of technical, organizational, social and psychological, legal character are revealed. Recommendations about development of institutional repositories for increase of use of opportunities in research works are made.
Keywords: digital library; institutional repository; OpenDOAR; ROAR; Ranking Web of Repositories; statistics module